Climatic Aptitude Evaluation for Grapevine Cultivation in Pão de Açúcar, Alagoas - Pedrosa, Douglas Leonardo Sales; Correia Filho, Washington L. F.; Gonçalves, João P. N.; Pereira, Lícia K. A.; Silva, Fabrício D. D. S. (Revista Geama, 2017)
The grapes production in Brazil is comprised in southeastern and southern regions and also in the semi-arid Pernambuco. Environmental, climatic and even human factors influence on quality of grape production, which are sensitive to weather changes. In Alagoas State, a pilot project was carried out for Municipalities of Rio Largo, Pão de Açúcar and Delmiro Gouveia between 2013 to 2015 years; but the results were incipient. This work evaluated the climatic aptitude for grapevine cultivation for municipality of Pão de Açúcar. For climate characterization, three indices of the Geoviticure Multicriteria Climatic Classification System (MCC) were adopted: Heliothermic (HI), Cold Night (CI) and Dryness (DI), considering different cycles during the year. The Zuluaga Index (IZ) was also used to evaluate the risk of incidence of fungal diseases of the vine, especially in relation at mildew incidence (Plasmoparaviticola), a major disease in humid regions. According on CI, DI and ZI indices, the municipality of Pão de Açúcar presented climatic aptitude for vines production with highest quality potential between August to January months, classified as preferential for all indexes analyzed.